Pengaruh Video Marketing, Harga dan Kualitas Produk Terhadap Minat Beli Pengguna Marketplace Shopee - Citrawati, Fonny Dwi; Yulianto, Mochamad Rizal; Febriansah, Rizky Eka; Indayani, Lilik (Ekonomis: Journal of Economics and Business, 2024)
This research aims to analyze the influence of video marketing, price and product quality partially and simultaneously on the buying interest of Shopee marketplace users in Sidoarjo Regency. The sample used in this research was 100 respondents. This research uses an associative explanatory method, this sampling uses a non-probability sampling method, known as purposive sampling with the data analysis approach applied is multiple linear regression, and is calculated using the Slovin formula. The results obtained show that simultaneously the video marketing, price and product quality variables have a positive and significant effect on the buying interest of Shopee marketplace users, but partially only the video marketing variable has no significant effect on the buying interest of Shopee marketplace users.